"Life Is Getting Better": Understanding Stabilizing Factors in Conservative Christian Families Post-Coming Out. Issue 2 (15th March 2021) - Drumm, René D.; Sedlacek, David A.; VanderWaal, Curtis J.; Trecartin, Shannon M.; Carbonell, Nancy J.
Abstract: This article explores the perceptions of Millennial-age LBGTQ + individuals raised in conservative Christian families (Seventh-day Adventist) about their coming out experiences with family members. The analysis examines six strategies that participants identified as helping regain family equilibrium post-coming out. These strategies included: parent's expression of unconditional love, passing of time, having a long-term relationship with a partner, communicating openly with parents, creating distance and independence from parents, and avoiding the LGBTQ + topic entirely.